More fermionic supersymmetric Wilson loops in four dimensions - Hao Ouyang; Jun-Bao Wu (Physics Letters B, 2024)
We construct supersymmetric fermionic Wilson loops along general curves in four-dimensional N=4 super Yang-Mills theory and along general planar curves in N=2 superconformal SU(N)×SU(N) quiver theory. These loops are generalizations of the Zarembo loops and are cohomologically equivalent to them. In N=4 super Yang-Mills theory, we compute their expectation values and verify the cohomological equivalence relation up to the order g4 in perturbation theory.